Identifying apartment buildings with potential heating issues Master of Science Thesis in Complex Adaptive Systems - Rooij, Joris van (My University, 2011)
The residential sector in Sweden uses a large amount of energy for heating and hot water. Sweden as well as all other European countries need to reduce its energy consumption with 9% by 2016. It is important to make sure that this heating is done in an optimal way in order to meet this demand. A method to identify buildings with possible heating problems is described in this thesis. The method uses analysis on the energy signature of buildings in order to construct parameters that point out buildings with possible problems. The method is applied to a set of 352 apartment buildings located in Gothenburg. The results show that a very large part of the set shows signs of possible heating problems.
Keywords: Fysik; Physical Sciences